Previous Crop and Cultivar Effects on Methane Emissions from Drill-Seeded, Delayed-Flood Rice Grown on a Clay Soil - Alden D. Smartt; Kristofor R. Brye; Christopher W. Rogers; Richard J. Norman; Edward E. Gbur; Jarrod T. Hardke; Trenton L. Roberts (Applied and Environmental Soil Science)
Due to anaerobic conditions that develop in soils under flooded-rice (Oryza sativa L.) production, along with the global extent of rice production, it is estimated that rice cultivation is responsible for 11% of global anthropogenic methane (CH4) emissions. In order to adequately estimate CH4 emissions, it is important to include data representing the range of environmental, climatic, and cultural factors occurring in rice production, particularly from Arkansas, the leading rice-producing state in the US, and from clay soils. The objective of this study was to determine the effects of previous crop (i.e., rice or soybean (Glycine max L.)) and cultivar (i.e., Cheniere (pure-line, semidwarf), CLXL745 (hybrid), and Taggart (pure-line, standard-stature)) on CH4 fluxes and emissions from rice grown on a Sharkey clay (very-fine, smectitic, thermic Chromic Epiaquerts) in eastern Arkansas. Rice following rice as a previous crop generally had greater (p<0.01) fluxes than rice following soybean, resulting in growing season emissions (p<0.01) of 19.6 and 7.0 kg CH4-C ha−1, respectively. The resulting emissions from CLXL745 (10.2 kg CH4-C ha−1) were less (p=0.03) than those from Cheniere or Taggart (15.5 and 14.2 kg CH4-C ha−1, resp.), which did not differ. Results of this study indicate that common Arkansas practices, such as growing rice in rotation with soybean and planting hybrid cultivars, may result in reduced CH4 emissions relative to continuous rice rotations and pure-line cultivars, respectively.